Usability Evaluation of Hospital Information Systems in Hospitals Affiliated with Mashhad University of Medical Sciences, Iran - Farahnaz Sadoughi; Masoumeh Khoshkam; Sayedeh Raziyeh Farahi (مدیریت اطلاعات سلامت, 2012)
Introduction: Hospital information systems (HISs) are computerized systems used as electronic tools for managing patient information. Usability is necessity for the success and acceptability of HISs and can enhance the quality of provided care. This study aimed to evaluate the usability of HISs in Hospitals affiliated with Mashhad University of Medical Sciences (Iran).